Photoinduced changes in the transport properties of oxygen-deficient YBa2Cu3Ox - Nieva, G. (1992)
Fil: Nieva, G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; University of California; Estados Unidos